FEATURES OF SITUATIONAL ANXIETY IN THE EDUCATIONAL ACTIVITY OF STUDENTS OF TSTU (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The work is devoted to the study of reactive or situational anxiety, which arises as an emotional reaction of students to various, most often socio-psychological stress factors. The study involved 218 first-year students of the Tashkent State Technical University named after Islam Karimov. The authors conducted a study of the level of situational anxiety of students engaged in aerobics at the university. To improve the efficiency of the educational process in the specialization "Aerobics", an attempt was made to create a comfortable educational environment for the student, which would minimize the negative manifestations of situational anxiety. The results of testing the level of situational anxiety were considered as an indicator of students' adaptability to aerobics in order to improve the organization of the educational process.